Association between the life’s essential 8 health behaviors score and all-cause mortality in cardiovascular-kidney-metabolic syndrome patients - Dingyuan Tu; Dingyuan Tu; Xiaoli Zuo; Ping Li; Jianming Wang (Frontiers in Nutrition)
BackgroundCardiovascular-kidney-metabolic (CKM) syndrome, a novel and multistage disorder recently proposed by the American Heart Association (AHA), highlights the intricate connection between cardiovascular, renal, and metabolic illnesses. Poor CKM health is highly prevalent in the U.S. We aimed to examine the association of Life’s Essential 8 (LE8), the AHA’s key measures for improving and maintaining cardiovascular health (CVH), with all-cause mortality among U.S. CKM syndrome patients.MethodsThis population-based prospective cohort study analyzed data of adults in the National Health and Nutrition Examination Survey from 2011 to 2018, with linked mortality information until 2019. LE8 score, which included four health behaviors and four health factors, was categorized into low (0–49), moderate (50–79), and high (80–100) CVH. Five CKM syndrome stages (stages 0–4) were defined according to the 2023 AHA guidelines, with advanced (stages 3 or 4) and non-advanced (stages 1 or 2) disease. Multivariable Cox regression and restricted cubic spline models were used to assess the associations.ResultsAmong 11,638 CKM syndrome patients (2,060 advanced stages), 831 deaths occurred over a median follow-up of 5.0 years. Interestingly, the relationship between total LE8 score and all-cause mortality was only significant in advanced CKM syndrome patients, while not significant in non-advanced CKM syndrome patients. Further analyses of LE8 subscales revealed that advanced CKM syndrome patients with moderate and high LE8 health behaviors score exhibited a reduced risk of all-cause mortality (moderate: hazard ratio, 0.52; 95% confidence interval, 0.39–0.70; high: 0.35; 0.24–0.49), as well as non-advanced CKM syndrome patients (moderate: 0.75; 0.55–0.98; high: 0.38; 0.24–0.59). Population attributable fraction suggested that 22.5 and 23.9% of all-cause mortality attributed to poor or moderate LE8 health behaviors score could be avoided if high score was achieved in advanced and non-advanced CKM syndrome patients.ConclusionOur study revealed a significant association between the LE8 health behaviors score and all-cause mortality in both advanced and non-advanced CKM syndrome patients, underscoring the value of this score in enhancing risk management approaches for CKM syndrome patients in future research and clinical practice.